Evektivitas Pengolahan Tanah dan Pengapuran Terhadap Pertumbuhan dan Produksi Kacang Merah (Phaseolus vulgaris L) - Aminah; Nuraeni (Journal Galung Tropika, 2024)
Soil is an essential factor in cultivating plants, which, apart from being a planting medium, also supplies food in the form of nutrients. For successful cultivation, farmers should know the condition of the soil before planting. One of the most important things is the soil acidity level (pH) and the type of soil that will be used for planting. The research aimed to determine the effect of soil processing and liming on the growth and production of red bean plants. The research was carried out in Bontomanai Village, Bungaya District, Gowa Regency, at an altitude of ± 400 meters above sea level from May to December 2023. The research used a Factorial Randomized Block Design with 2 factors. The first factor is soil processing, with 2 treatment levels: No tillage (control) and tillage (Hoeing). The second factor is the lime dose, with 4 levels of treatment, namely without liming (control), 1 ton/ha (0.1 kg/plot), 2 tons/ha (0.2 kg/plot), 3 tons/ha (0 .3 kg/plot). There were 8 combinations, and each treatment combination was repeated 3 times, so that 24 treatment combination units were obtained. Each treatment combination unit used 10 plants and 3 sample plants. The research results showed that tillage had a better effect than no tillage at a weight parameter of 100, namely 41.30 gr. Liming at a dose of 3 tons per hectare had the best effect on plant height parameters, namely 47.68 cm. The interaction between soil processing and liming at a dose of 3 tons/ha gave the best effect on seed weight per planting, 24.93 grams, seed weight per plot of 0.28 kg, and seed production per hectare, namely 2.8 tons/ha.